2022
DOI: 10.3390/jmse10050560
|View full text |Cite
|
Sign up to set email alerts
|

A Multihull Boat’s Fatigue Analysis at Early Design Phase

Abstract: Fatigue analysis and life cycle prediction of a naval craft or a commercial ship are one of the most critical phases of structural integrity calculations. Many structural failures have occurred due to insufficient structural design, production methods, and inappropriate operational environmental conditions. As a result of the deterioration of the structural integrity, the occurrence of both vital and economic losses becomes inevitable. This paper emphasises the importance of fatigue and life cycle analyses at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Kabakcioglu [10] discussed the effects of the sea state, environmental conditions, and materials on the fatigue performance of ships, emphasizing that fatigue analysis and life cycle prediction are critical for structural integrity calculations of naval ships and vessels. The study focused on fatigue calculations and life prediction using the Palmgren-Miner method, and it concluded that consideration of the fatigue life prediction in the early design stage can help identify the critical locations of potential fatigue cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Kabakcioglu [10] discussed the effects of the sea state, environmental conditions, and materials on the fatigue performance of ships, emphasizing that fatigue analysis and life cycle prediction are critical for structural integrity calculations of naval ships and vessels. The study focused on fatigue calculations and life prediction using the Palmgren-Miner method, and it concluded that consideration of the fatigue life prediction in the early design stage can help identify the critical locations of potential fatigue cracks.…”
Section: Introductionmentioning
confidence: 99%